Optimizing T4 DNA polymerase conditions enhances the efficiency of one-step sequence- and ligation-independent cloning - Mohammad Nazrul Islam; Kyeong Won Lee; Hyung-Soon Yim; Seong Hyuk Lee; Hae Chang Jung; Jung-Hyun Lee; Jae-Yeon Jeong (BioTechniques)
Previously, we developed a one-step sequence- and ligation-independent cloning (SLIC) method that is simple, fast, and cost-effective. However, although one-step SLIC generally works well, its cloning efficiency is occasionally poor, potentially due to formation of stable secondary structures within the single-stranded DNA (ssDNA) region generated by T4 DNA polymerase during the 2.5 min treatment at room temperature. To overcome this problem, we developed a modified thermo-regulated one-step SLIC approach by testing shorter T4 DNA polymerase treatment durations (5 s–2.5 min) over a wide range of temperatures (25–75°C). The highest cloning efficiency resulted when inserts with homology lengths <20 bases were treated with T4 DNA polymerase for 30 s at 50°C. This briefer T4 polymerase treatment at a higher temperature helps increase cloning efficiency for inserts with strong secondary structures at their ends, increasing the utility of one-step SLIC for the cloning of short fragments.